Biochemical and Physiological Response During Oxidative Stress (IntechOpen, 2025)
The present volume provides an all-around overview of the complicated system that is oxidative stress, from basic knowledge at the level of the molecular mechanism of the process itself right through to complex relationships connecting it with a broad spectrum of pathologies in light of consequences to human health and ecological balance. It shall give substantial scientific support for stimulating further research with open prospects to get innovative preventive and therapeutic strategies.